Outer Membrane Protein 25 of Brucella Activates Mitogen-Activated Protein Kinase Signal Pathway in Human Trophoblast Cells - Jing Zhang; Yu Zhang; Zhiqiang Li; Jing Liu; Xuehua Shao; Changxin Wu; Yong Wang; Kaisheng Wang; Tiansen Li; Laizhen Liu; Chuangfu Chen; Hui Zhang (Frontiers in Veterinary Science, 2017)
Outer membrane protein 25 (OMP25), a virulence factor from Brucella, plays an important role in maintaining the structural stability of Brucella. Mitogen-activated protein kinase (MAPK) signal pathway widely exists in eukaryotic cells. In this study, human trophoblast cell line HPT-8 and BALB/c mice were infected with Brucella abortus 2308 strain (S2308) and 2308ΔOmp25 mutant strain. The expression of cytokines and activation of MAPK signal pathway were detected. We found that the expressions of tumor necrosis factor-α, interleukin-1, and interleukin-10 (IL-10) were increased in HPT-8 cells infected with S2308 and 2308ΔOmp25 mutant. S2308 also activated p38 phosphorylation protein, extracellular-regulated protein kinases (ERK), and Jun-N-terminal kinase (JNK) from MAPK signal pathway. 2308ΔOmp25 could not activate p38, ERK, and JNK branches. Immunohistochemistry experiments showed that S2308 was able to activate phosphorylation of p38 and ERK in BABL/c mice. However, 2308ΔOmp25 could weakly activate phosphorylation of p38 and ERK. These results suggest that Omp25 played an important role in the process of Brucella activation of the MAPK signal pathway.